Study of the effect of polymer network structure on thermal and mechanical properties of crosslinked (meth)acrylates - cis-hexahydrophthalic anhydride derivatives - Podgórski, M.; Księżopolski, J. (Polimery, 2021)
The novel multifunctional monomers, glycidyl esters of trimethacrylic acid or dimethacrylic-acrylic one were prepared via three-stage synthesis method (Table 1, Fig. 1). Their homopolymers or copolymers with styrene were obtained in photopolymerization processes. Mechanical and thermal properties of the polymerizations products (Fig. 2-5) were evaluated. The degree of conversion of unsaturated bonds was determined (Fig. 6, 7) and dynamic thermal analyses were done (Table 2). Quality evaluation of the degree of structural heterogeneity of polymer networks obtained has been done and the effect of heterogeneity on the product properties was discussed.